Physiological Correlates of Neurobehavioral Disinhibition that Relate to Drug Use and Risky Sexual Behavior in Adolescents with Prenatal Substance Exposure - Conradt, Elisabeth (Dev Neurosci, 2014)
Physiological correlates of behavioral and emotional problems, substance use onset and initiation of risky sexual behavior have not been studied in adolescents with prenatal drug exposure. We studied the concordance between baseline respiratory sinus arrhythmia (RSA) at age 3 and baseline Cortisol levels at age 11. We hypothesized that children who showed concordance between RSA and Cortisol would have lower neurobehavioral disinhibition scores which would in turn predict age of substance use onset and first sexual intercourse. The sample included 860 children aged 16 years participating in the Maternal Lifestyle Study, a multisite longitudinal study of children with prenatal exposure to cocaine and other substances. Structural equation modeling was used to test pathways between prenatal substance exposure, early adversity, baseline RSA, baseline Cortisol, neurobehavioral disinhibition, drug use, and sexual behavior outcomes. Concordance was studied by examining separate male and female models in which there were statistically significant interactions between baseline RSA and Cortisol. Prenatal substance exposure was operationalized as the number of substances to which the child was exposed. An adversity score was computed based on caregiver postnatal substance use, depression and psychological distress, number of caregiver changes, socioeconomic and poverty status, quality of the home environment, and child history of protective service involvement, abuse and neglect. RSA and Cortisol were measured during a baseline period prior to the beginning of a task. Neurobehavioral disinhibition, based on composite scores of behavioral dysregulation and executive dysfunction, substance use and sexual behavior were derived from questionnaires and cognitive tests administered to the child. Findings were sex specific. In females, those with discordance between RSA and Cortisol (high RSA and low Cortisol or low RSA and high Cortisol) had the most executive dysfunction which, in turn, predicted earlier initiation of alcohol by age 16. Among boys, there also existed a significant baseline RSA by baseline Cortisol interaction. Boys with low baseline RSA and high baseline Cortisol had the highest levels of behavioral dysregulation. This increase in behavioral dysregulation was in turn related to initiation of alcohol use by age 16 and lower age of first sexual intercourse. We found sex-specific pathways to the initiation of alcohol use and risky sexual behavior through the combined activity of parasympathetic and neuroendocrine functioning. The study of multiple physiological systems may suggest new pathways to the study of age of onset of substance use and engagement in risky sexual behavior in adolescents.